Thalassemia-Beta major-Case report - Vesna Ambarkova; Tina Krmzova; Zoran Nonkulovski (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2021)
Beta thalassemia (β thalassemia) is a group of inherited blood disorders. Case report A 17-year old boy accompanied by medical support staff visited our Department for preventive and pediatric dentistry within the University Dental Center Ss.Pantelejmon in Skopje, due to a dental pain which comes from the first molar tooth(36) of the low jaw from the left side. From the accompanying documentation we saw that the boy has congenital beta thalassemia major and was admitted to the Department for Hematology within University State Hospital Mother Theresa a month ago. The boy was hospitalized in an agreed term for realization of allogeneic bone marrow transplantation, from a related donor (sister). Dental problems in patients with thalassemia are common and should not be neglected. With the introduction of stem cell transplantation from a related donor, a bright future has been opened for children with thalassemia in the Republic of North Macedonia.